Recruitment in the gig economy: attraction and selection on digital platforms. Issue 19 (28th October 2021) - Williams, Penny; McDonald, Paula; Mayes, Robyn
Abstract: Digital platform work is undertaken as short term, temporary 'gigs' mediated by platform businesses that connect self-employed workers to clients via an app. Platforms manage and profit from labour-capital relations yet are not employers. This study explores the extent to which, and how, digital platforms implement human resource practices to attract and select self-employed platform workers. A qualitative, comparative analysis of the website content, and terms and conditions documents of 17 digital platforms offering virtual work in graphic design, and in-person care work in Australia was undertaken. The findings reveal how platforms combine traditional recruitment practices with new forms of algorithmic shortlisting that result in industry-specific risks for platform workers. More broadly, the study provides insights into the recruitment practices used by digital platform businesses and contributes to knowledge of how the roles and responsibilities of human resource management are reconfigured in digital platform work.